2013
DOI: 10.3892/or.2013.2807
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-27a functions as a tumor suppressor in esophageal squamous cell carcinoma by targeting KRAS

Abstract: microRNAs (miRNAs) have been suggested to play a vital role in regulating tumor progression and invasion. However, the expression of miR-27a in esophageal squamous cell carcinoma (ESCC) and its effect on the tumorigenesis of ESCC are unclear. In the present study, we found that miR-27a was downregulated in esophageal carcinoma cell lines and ESCC specimens with lymph node metastasis. Furthermore, we demonstrated that miR-27a binds to the 3'-untranslated region (UTR) of KRAS and inhibits the expression of the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
5
22
0
1
Order By: Relevance
“…MiR‐27a previously showed inconsistent results in various cancers. While serving as a tumour suppressor in oesophageal cancer and liver cancer, it has been reported to be a promoting factor of tumorigenesis in gastric cancer . This was confirmed in our study, where a positive association was seen between miR‐27 and gastric cancer but a negative association with breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…MiR‐27a previously showed inconsistent results in various cancers. While serving as a tumour suppressor in oesophageal cancer and liver cancer, it has been reported to be a promoting factor of tumorigenesis in gastric cancer . This was confirmed in our study, where a positive association was seen between miR‐27 and gastric cancer but a negative association with breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, miR‐27a has been shown to negatively regulate FOXO1 , RYBP , and ZBTB10 , which regulate apoptosis and cell cycle progression . In contrast, some studies have reported that miR‐27a functions as a tumor suppressor in esophageal squamous cell carcinoma by regulating KRAS, in renal cell carcinoma by targeting EGFR and in prostate cancer by targeting MAP2K4 . However, miR‐27a functions and target genes in lung cancer are not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-27a has been investigated in several types of cancer and comes into inconsistent results. MiR-27a functions as a tumor suppressor in ESCC and hepatocellular carcinoma, while serves as promoting factor in gastric tumorigenesis2930. Therefore, we assume that miR-27a plays pleiotropic signaling roles in regulating tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%